Food-Grade Expression of Manganese Peroxidases in Recombinant Kluyveromyces lactis and Degradation of Aflatoxin B1 Using Fermentation Supernatants - Xia, Yu; He, Rui; Sun, Ying; Zhou, Hangyu; Gao, Minjie; Hu, Xiuyu; Cui, Xiaobing; Cheng, Qianqian; Wang, Zhouping (Frontiers in Microbiology, 2022)
Aflatoxins are naturally occurred high-toxic secondary metabolites, which cause worldwide environmental contaminations, wastes of food and feed resources, and severely threaten human health. Thus, the high-efficient methods and technologies for detoxification of aflatoxins are urgently needed in a long term. In this work, we report the construction of recombinant Kluyveromyces lactis strains GG799(pKLAC1-Phsmnp), GG799(pKLAC1-Plomnp) and GG799(pKLAC1-Phcmnp), and then the food-grade expression of the 3 manganese peroxidases in these strains, followed by the degradation of aflatoxin B1 (AFB1) using the fermentation supernatants. The inducible expression process of the optimal recombinant strain GG799(pKLAC1-Phcmnp), and the aflatoxin B1 degradation process were both optimized in detail. After optimization, the degradation ratio reached 75.71%, which was an increase of 49.86% compared to the unoptimized results. The degradation product was analyzed and determined to be AFB1-8,9-dihydrodiol. The recombinant strain GG799(pKLAC1-Phcmnp) supernatants degraded more than 90% of AFB1 in the peanut samples after twice treatments. The structural computational analysis for further mutagenesis of the enzyme PhcMnp was also conducted in this work. The food-grade recombinant yeast and the enzyme PhcMnp have potential to be applied in food or feed industry.